Regulated microbe vaccines: from concept to (pre-clinical) reduction to practice - Richard Voellmy; David C Bloom; Nuria Vilaboa (Expert Review of Vaccines)
Introduction Vaccines to prevent important infections involving, e.g. influenza viruses, severe acute respiratory syndrome-causing coronaviruses (e.g. SARS-CoV-2), respiratory syncytial viruses (RSV), and human immunodeficiency viruses (HIV) have remained insufficiently effective or are not available at all. Regulated microbes constitute novel vaccine platforms that may be employed for the development of more potent and/or more broadly effective vaccines.Areas covered We review the development and characterization of the vaccine potential of replication-competent controlled herpesviruses (RCCVs) which represent the first examples of regulated microbes used as vaccines.Expert opinion The RCCVs developed to date are suitable for application to the skin and can be activated deliberately to replicate efficiently, but only transiently, in the administration site. Without activation, the RCCVs are incapable of replicating in the nervous system and elsewhere. The RCCVs were found to induce potent anti-herpetic immune responses in mice. Vaccination with RCCVs expressing an influenza virus hemagglutinin broadly protected animals against lethal influenza virus challenges. This protection appeared to be at least in part antibody-mediated. These findings support a rational expectation that RCCVs may be developed into universal, non-seasonal vaccines against influenza and, possibly, against other rapidly evolving pathogens.